The Concept of Science in Islamic Tradition: Analytical Studies of Syed Naquib Al-Attas on Knowledge - Nirhamna Hanif Fadillah; Amir Reza Kusuma; Najib Rahman Rajab al-Lakhm (University of Darussalam Gontor, Indonesia, 2023)
Secularism is a thought born of Western perspectives and experiences, which has had a negative impact on contemporary science. The bad impact is based on the conception of secularism itself, in the form of disenchantment of nature, or the emptying of the universe from religious and spiritual values; desacralization of politics or political exclusion from religious and spiritual elements. Also, deconsecration of false or relativizing human values, so that there are no absolutes in a truth. For this reason, Syed Naquib al-Attas sees the need for the Islamization of knowledge to answer the problem of secularism. Through a library research type study with a descriptive-analytical approach, it can be concluded that al-Attas' Islamization of knowledge answers the problem of secularism in science with three things. Therefore, the composition of the concept of Al-Attas science is built on an Islamic worldview, it is hoped that a Muslim will use his Islamic worldview in viewing reality and truth. both propositions and ontologies. The method of acquiring knowledge is also different from the Western concept, where al-Attas explains that there are several intermediaries, namely healthy senses, khabar sadiq, common sense, and intuition.